Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s00018-021-03785-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of neuronal dysfunction in HIV-associated neurocognitive disorders

Abstract: HIV-associated neurocognitive disorder (HAND) is characterized by cognitive and behavioral deficits in people living with HIV. HAND is still common in patients that take antiretroviral therapies, although they tend to present with less severe symptoms. The continued prevalence of HAND in treated patients is a major therapeutic challenge, as even minor cognitive impairment decreases patient’s quality of life. Therefore, modern HAND research aims to broaden our understanding of the mechanisms that drive cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 196 publications
(242 reference statements)
2
37
0
Order By: Relevance
“…During the past decade, there has been an increasing interest in the mechanism, diagnosis, and treatment of HAND. However, the effective treatment of HAND has not been established, which indicates that the pathogenesis underlying the HAND remains controversial and unclear ( Irollo et al, 2021 ). In the absence of updated neuropathology research, much of the knowledge on HAND will have to rely on advanced neuroimaging technology, which can provide insights on macrolevel brain changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, there has been an increasing interest in the mechanism, diagnosis, and treatment of HAND. However, the effective treatment of HAND has not been established, which indicates that the pathogenesis underlying the HAND remains controversial and unclear ( Irollo et al, 2021 ). In the absence of updated neuropathology research, much of the knowledge on HAND will have to rely on advanced neuroimaging technology, which can provide insights on macrolevel brain changes.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are necessary to validate whether the abnormalities described in our study are related to the pathogenesis of this condition. Previous research reported that reversing synaptic cartilage damage in animal models can restore cognitive function, so it highlights a promising treatment approach that has the potential to treat HAND ( Irollo et al, 2021 ). Moreover, the studies on the manifestations and mechanisms of synaptic damage and functional and structural network abnormity in preclinical HAND patients and experimental models may contribute to developing safe and effective therapeutic methods that reverse subtle neuropathological changes and cognitive impairment, while longitudinal research might assess the risk factors for developing HAND and the response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Continued research on the manifestation and mechanisms of neurological injury in HAND patients is needed. Animal models will be critical to help develop safe and effective therapies that reverse neuropathology and cognitive impairment [8].…”
Section: Animal Models Of Hiv Infection In the Cnsmentioning
confidence: 99%
“…Consequently, HIV infection can often be associated with neurological damage, including neurocognitive impairment and HIV-associated dementia (HAD) [6,7]. Typical symptoms include loss of concentration, attention, and memory, irritability, depression, and slowed movements [8]. The severity of the symptoms can range from asymptomatic to HAD in the most severe cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation